THE EFFECT OF STAIRCASE MEDIA ON UNDERSTANDING THE CONCEPT OF LENGTH MEASUREMENT IN ELEMENTARY SCHOOL - anisa zatun nitha qoini; naura anandia ghatsa; silvia nuril mala; susia utami; wulan puspita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lampung, 2025)
Grade 3 students at SDN 3 Tanjung Raja still have difficulty in understanding the material on measuring length. The purpose of this study was to determine children's understanding of the ladder teaching media. The type of research used was quantitative with a method of distributing questionnaires to respondents, namely teachers at SD Negeri 3 Tanjung Raja. Based on the results of the questionnaire that has been distributed, it shows that with the presence of ladder teaching media, it is easier for students to understand the material for measuring length, besides that, students also enjoy learning. Mathematics learning on the material on measuring length can use ladder teaching media because it can help students understand the material on measuring length.